ANALISIS PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN, DAN SIKAP PENGGUNAAN TERHADAP MINAT PERILAKU PENGGUNAAN BILLING SYSTEM (STUDI PADA WAJIB PAJAK KANTOR PELAYANAN PAJAK PRATAMA MALANG UTARA) - Andrian, Agus (Jurnal Mahasiswa Perpajakan, 2014)
This research uses TAM as a basic model of hyphothesis. The variable which are use in this research is perceived usefulness, perceived ease of use, attitude towards, and behavioral intention. The goal is to know perceived usefulness, perceived ease of use, and attitudes towards the use of the taxpayerâ€™s interest to use the Billing System Â . This research uses descriptive method quantitative approach. Data collection is done using random sampling techniques. The data used are primary data obtained by using a questionnare. The subject of this research is the taxpayer listed on KPP Pratama North Malang. The sample used in this research amounted 100 respondents and data analysis using SPSS program version 21.0. The result of this research indicates that all the hypothesis are accepted. The first hypothesis shows that Perceived ease of use significantly influential to perceived usefulness. The second hyphotesis shows that perceived usefulness significantly influential to attitude towards. The third hyphotesis shows that perceived ease of use significantly influential to attitude towards. The fourth hypothesis shows that attitude towards significantly influential to behavior intention. The fifth hyphotesis shows that perceived usefulness significantly influential to behavioral intention. Keywords: Billing System, Technology Acceptance Model (TAM), Perceived Usefulness, Perceived Ease of Use, Attitude Toward, Behavioral, Intention